Walking backwards in sports training аnd medical rehabilitation - A. Klemenov (National Electronic Information Consortium (NEICON), 2020)
In recent years backward walking is increasingly used in sports and medicine. During sports training backward walking can be used as one of the methods of fitness. Backward walking increases the cardiovascular and respiratory loads and aerobic and anaerobic capacities of the organism. Backward walking is associated with less overload of knee joints. It is also one of the few natural ways of strengthening the quadriceps. Backward walking training has found its application in rehabilitation programs for different categories of neurological patients with the aim of restoring sustainable body position and gait. Backward walking is used to elaborate the correct pattern of gait in children with cerebral palsy, in persons with hemiplegia after stroke, in patients suffering from Parkinson's disease and multiple sclerosis, in spinal cord injured patients. There is an information about the application of backward walking exercises in diabetic foot syndrome in order to reduce a plantar pressure and in physical rehabilitation of postoperative patients. Tests with backward walking are used for diagnostic purposes - to assess the severity of impaired coordination and motor skills in post-stroke patients and in Parkinson's disease, to identify the minimal walking impairment in persons with multiple sclerosis and for probability of falling prediction in elderly individuals and patients with dizziness.